A prospective cohort study on the association between neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios and gestational diabetes mellitus in Chinese pregnant women - Zhao, Xin; Sun, Jianbin; Yuan, Ning; Zhang, Xiaomei (Frontiers in Endocrinology, 2025)
AimThis study investigated whether neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in early pregnancy correlate with subsequent development of gestational diabetes mellitus (GDM).MethodsThis prospective cohort study enrolled 1,200 pregnant women during their first trimester at Peking University International Hospital between December 2017 and March 2019. All participants underwent oral glucose tolerance testing (OGTT) at 24-28 weeks gestation. Complete blood counts obtained in the first trimester were analyzed for NLR and PLR values. Participants were categorized into GDM (n=227) and non-GDM (n=973) groups based on International Association of Diabetes and Pregnancy Study Groups criteria.ResultsWomen who developed GDM exhibited significantly higher first-trimester levels of neutrophils, lymphocytes, platelets, NLR, and PLR (all p<0.05) compared to women without GDM. First-trimester NLR and PLR values positively correlated with second-trimester blood glucose levels at 0, 60, and 120 minutes during OGTT (all p<0.05). The optimal cut-off values for predicting GDM were 3.89 for NLR (sensitivity 76.05%, specificity 36.56%) and 148.11 for PLR (sensitivity 68.72%, specificity 68.65%). A multivariate predictive model incorporating NLR, PLR, age, parity, BMI, blood lipids, and uric acid demonstrated 78.39% sensitivity, 73.83% specificity, and 78.87% accuracy with an area under the curve of 0.79 (95% CI: 0.71, 0.86).ConclusionsFirst-trimester NLR and PLR represent independent risk factors for GDM development. These readily available inflammatory markers may have value for early GDM risk assessment and aid in targeting preventive interventions